Single-Image Shadow Detection using Quaternion Cues. (27th January 2018) - Hiary, Hazem; Zaghloul, Rawan; Al-Zoubi, Moh'd Belal
Abstract: Shadow detection is an important pre-processing step often used in scene interpretation or shadow removal applications. In this paper, we propose a single-image shadow detection method. Many other methods use multiple images; we use a quaternion representation of colour images to extract shadows from only one input image. The generation of the final binary shadow mask is done via automatic threshold selection. Evaluation is carried out qualitatively and quantitatively over three challenging datasets of indoor and outdoor natural images. The results of qualitative assessment were consistent with the statistical results, where the proposed method improves the performance of shadow detection when compared with state-of-the-art methods.